MEKANISME CORPORATE GOVERNANCE DAN KINERJA KEUANGAN TERHADAP SUSTAINABILITY REPORTING - Dwi Sri Fathonah (Accounting and Finance Studies, 2022)
This study aims to analyze the effect of the board of commissioners, audit committee, foreign ownership, family ownership, institutional ownership, and financial performance using proxies of profitability on sustainability reporting in Indonesian group business companies listed on the IDX for the 2018-2019 period. The sample in this study were 28 Indonesian business group companies listed on the IDX for the 2018-2019 period. Thus, there are 56 observational data. The sampling technique used was purposive sampling. The analysis used in this research is panel data regression analysis with the help of the Eviwes 10 application. Based on data analysis carried out by panel data regression analysis, it showsthat the independent variables of the board of commissioners and family ownership have a negative effect on the disclosure of sustainability reporting in group business companies in Indonesia. Meanwhile, the results for the audit committee variables, foreign ownership, institutional ownership, and profitability did not affect the sustainability reporting disclosures in the Indonesian group business companies